ON MENELAUS' SPHERICS III.5 IN ARABIC MATHEMATICS, II: NAṢĪR AL-DĪN AL-ṬŪSĪ AND IBN ABĪ JARRĀDA. Issue 1 (13th February 2015) - Rashed, Roshdi; Papadopoulos, Athanase
Abstract In his Sphaerica, Menelaus did not prove Proposition III.5 which is particularly important. He only gave an outline of a proof. Once the Sphaerica were translated into Arabic, mathematicians, starting from the end of the 9th century on, took up this proof. That was made possible to Ibn ʿIrāq thanks to the development of spherical geometry. A first paper contained the history of his contribution. Two other mathematicians, from the 13th century – Naṣīr al-Dīn al-Ṭūsī and Ibn Abī Jarrāda – worked out again the proof of the proposition with the help of Menelaus' book and of the new acquisitions of Ibn ʿIrāq. This is the subject of this second paper.